Satyrium nepalense: A RARE MEDICINAL ORCHID OF WESTERN HIMALAYA (INDIA); PHYTOCHEMICAL SCREENING, ANTIMICROBIAL EVALUATION AND CONSERVATION STUDIES - Mishra, Abhay Prakash; Saklani, Sarla (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Satyrium nepalense is an endangered medicinal herb found at the higher altitude of 2400-5000m. Local inhabitant used tubers of Satyrium nepalense as an energetic tonic and as an important medicine to cure different type of fever in traditional health care system of Uttarakhand (INDIA). Present study was carried out to evaluate the phytochemical, antibacterial screening against four (Streptococcus mutans, Pseudomonas aeruginosa, Staphylococcus aureus and Klebsiella pneumoniae) microorganisms in methanolic extracts and habitat studies for conservation of S. nepalense. Tubers of Satyrium nepalense were extracted separately with methanol by hot extraction process using soxhlet apparatus. The extracts were subjected to Lyophilization to get dry extract and preserved in aseptic condition. The different group reagents used for phytochemical screening as dragendorffs’s for alkaloid, molisch’s test for carbohydrates, shinoda test for flavonoids etc. Antibacterial study was carried out by disc diffusion method. The highest zone of inhibition was recorded as 15.0±0.00 mm against Klebsiella pneumonia and 15.0±0.82 mm against Staphylococcus aureus. Phytochemical screening shows the presence of alkaloids, carbohydrates/glycosides, flavonoids and unsaturated sterols/triterpenes in Satyrium nepalense. The result indicates that methanolic extract of Satyrium nepalense shows potent antibacterial activity against all four bacterial strains.Key words: Uttarakhand, Satyrium nepalense, medicinal orchid, antibacterial, phytochemicals